Social elevators in education: problems and solutions - S. I. Chernykh (Высшее образование в России, 2018)
The article analyzes the role of social mobility in modern society, discusses the function of social elevators in education. The author dwells on the role of social elevators in combating inherited poverty and preservation of elites. Education is not the only one sphere of human activity that has the function of a social elevator, but it’s role is especially great at the present time. The author shows that due to the problems arising in this sphere only a small percentage of population can essentially raise their social status by means of education as a social elevator. Various factors that determine unequal access to education of representatives of different social strata are considered. The paper draws attention to the fact that the social еlevator should not be a basis for social parasitism. It should be a system that enables students to make high efforts and get good results. Social equity is appropriate only at a start of a career, but then it must become a basis for well-deserved distinction.